2007
DOI: 10.1016/j.jcrs.2006.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Bag-in-the-lens intraocular lens implantation in the pediatric eye

Abstract: The bag-in-the-lens implantation technique in children and babies was safe and kept the visual axis clear after cataract surgery. In the near future, 4.0 or 4.5 mm IOLs will be available that may improve the success rate of IOL implantation in the small eyes of babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 31 publications
5
47
0
2
Order By: Relevance
“…This confirms our preliminary results. 12 Visual axis reproliferation occurred in 3 eyes of children. In these cases, the capsule was not properly suspended in the lens groove and further surgery was required to resolve the proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms our preliminary results. 12 Visual axis reproliferation occurred in 3 eyes of children. In these cases, the capsule was not properly suspended in the lens groove and further surgery was required to resolve the proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the present study, we found no increased risk for severe adverse events. After the 1-year follow-up of the first 60 patients, there were no cases of visual axis reproliferation 6 and no signs of inflammatory reaction at the level of the anterior hyaloid; this was a concern in a previous study by Praveen et al 24 Interim visual axis reproliferation results after BIL IOL implantation in adults 25 and in children [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been published. This more exhaustive follow-up study confirms the previously published data.…”
Section: Discussionmentioning
confidence: 99%
“…The capsule's extreme elasticity makes it difficult to achieve a predetermined diameter, something that is important for correct IOL positioning, especially with an IOL that is capsule fixated. 7,16 Another challenge is the high rate of PCO in infants, which is close to 100% if the posterior capsule is left intact; this also increases the risk for amblyopia. 6 At present, the only way to prevent PCO is by performing a posterior capsulotomy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no software adapted for posterior capsulotomy, which makes it necessary to position the treatment zones manually. Animal studies and experiments with cadaver eyes have shown that capsulotomies created by the femtosecond laser are more tear 16,19 On the other hand, scanning electron microscopy has shown a much more irregular cutting pattern after laser capsulotomy. 16,20 In our study, however, there were no capsule tears.…”
Section: Discussionmentioning
confidence: 99%
“…Visual results are positive enough to advocate intraocular lens (IOL) implantation in children older than 2 years as an efficacious and safe procedure. [1][2][3][4] Intraocular lenses are routinely implanted in the capsular bag after cataract extraction; however, sulcus implantation and scleral fixation have also yielded successful results. [5][6][7] In most cases of pediatric cataract, the opaque lens material can easily be removed from the capsular bag by irrigation/aspiration (I/A) without the need for phacoemulsification.…”
mentioning
confidence: 99%